TIPOLOGI PENGGUNAAN LAHAN OLEH MASYARAKAT PADA ZONA PENYANGGA TAMAN NASIONAL AKETAJAWE LOLOBATA DI KABUPATEN HALMAHERA TIMUR - Lis Nurrani; M Bismark; Supratman Tabba (Pusat Penelitian dan Pengembangan Sosial, Ekonomi, Kebijakan dan Perubahan Iklim, 2014)
Role of buffer zone is vital for conservation and sustainability of a national park, because it can hinder from negative activity of the community to the conservation area. This research was conducted inAketajawe Lolobata National Park buffer zone. Aimed to obtain the ideal model of land management based on land use patterns, biophysical condition and wildlife habitat parameters. Sample villages and respondents determined by purposive sampling, with sampling intensity 10%. Research methods using combination of semi-structured interview technique and field survei. Scrutiny results revealed that Aketajawe Lolobata National Park buffer zone composed of green lane, interaction pathways and cultivation pathways. This zone is dominated by interaction pathway in the form of mixed garden, monoculture garden and intercropping garden with coconut as a major plant.While teak community forests which should be the main plant species on interaction pathways, it was found on cultivation pathways. Wildlife on community land use consists of 39 species of birds, five species of mammals, seven species of reptiles, two species of amphibians and various of insects and other water animals. Mixed garden is the most ideal land use patterns based on the criteria of land biological conservation and environmental availability as a wildlife habitat.